The role of the mathematical model of the complex assessment of the compatibility of combination of construction processes - Arutiunian, I.; Pastukhova, S.; Myleta, K.; Pastukhov, V. (Ways to Improve Construction Efficiency, 2024)
The scientific article defines the role of mathematical modeling in the assessment of construction production regarding the admissibility of a combination of processes. Special attention is paid to the comprehensive study of the stages of construction in order to identify the main types of work and identify possible ways of combining them. In addition, the existing methods of construction organization were analyzed. Based on the conducted research, the course of model development was determined. The article examines and analyzes the complex influence of organizational and technological factors that affect construction, develops a mathematical model of the researched process in the form of systems of equations connecting the indicators of the researched process and its variable parameters, the variation of which studies the behavior of the process. The need for the use of information technologies in a construction company, the development of a mathematical model of the resource planning process and the selection of suppliers, and the requirements for the development of an information system. Based on the received relationships of qualitative and quantitative parameters, a model is developed and an algorithm for its calculation is built. In connection with the above, it is obvious that the development of such a model will allow a comprehensive assessment of the admissibility of combining construction processes. Construction of objects is a process in which implementing organizations, suppliers and consumers of material and technical resources, vehicles and other elements interact in a complex relationship. At the same time, the performance of work is affected by many different, in particular random, factors. A mathematical model is proposed for their influence, which will allow taking into account the joint influence of various factors, taking into account random factors of influence. Consider the value of mathematical modeling during the analysis of a potential combination of processes in construction. We focus on the study of construction processes, identify the main stages of work and identify methods of combination. We will analyze the construction methods used and determine their modeling methods.